Optimizing optical thermometry with tri-doped Ba2GdV3O11 phosphors: Ratiometric and fluorescence lifetime analysis - Kachou, Ikhlas; Saidi, Kamel; Ekim, Utku; Dammak, Mohamed; Ersundu, Miray Celikbilek; Ersundu, Ali Ercin (CELL PRESS, 2024)
Optical sensor technology has undergone a transformative evolution with the advent of fluorescence ratio techniques (FIR) and fluorescence lifetime (FL) strategies, revolutionizing precision, performance, and reliability. This study delves into the synthesis of Ba 2 GdV 3 O 11 phosphors doped with Ho 3+ /Nd 3+ , Er 3+ , and Yb 3+ , employing the sol-gel method for upconverting material fabrication. A thorough investigation into the structural, morphological, and optical properties of the synthesized phosphors is conducted. Excitation at 980 nm unveils upconversion (UC) emissions across green and red spectra. The intensities of the observed emission bands for Ho 3+ , Nd 3+ , and Er 3+ demonstrate significant sensitivity to fluctuations in temperature. Temperature sensing relies on the 4 S 3/2 and 2 H 11/2 upconversion emissions bands, in addition to the emission lifetimes at 4 S 3/2 . Enhanced thermal sensitivity values are attained, reaching up to 1.03 % K -1 and 1.07 % K -1 using the FIR strategy, and up to 0.146 % K -1 and 0.47 % K -1 with the FL strategy for Ho 3+ / Er 3+ /Yb 3+ and Nd 3+ /Er 3+ /Yb 3+ tri-doped Ba 2 GdV 3 O 11 phosphors, respectively. Furthermore, the studied phosphors exhibit remarkable precision in detecting minute temperature changes (0.3 K), positioning them as promising candidates for precise temperature sensing. This study pioneers innovative methodologies to advance optical thermometry techniques, offering promising prospects for scientific and industrial applications reliant on precise optical temperature sensing.
Keywords: Optical temperature sensing; Upconversion luminescence; FIR; Fluorescence lifetime; UP-CONVERSION LUMINESCENCE; TEMPERATURE SENSING BEHAVIOR; UPCONVERTING NANOCRYSTALS; EMISSION; NANOPARTICLES; PERFORMANCE; POWER; Science & Technology - Other Topics